UPAYA MENGHINDARI DIKOTOMI ILMU MELALUI INTEGRASI PENDIDIKAN ISLAM DALAM PENDIDIKAN NASIONAL - Suswanto; Haris Riadi; Neng Sufia; Safna Febriyani; Halimatu Sa’diah; Gusti Erlina; Muhammad Suprapto (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
The dichotomy of education in Indonesia is a problem that requires immediate attention. This study uses qualitative methods through literature studies and observations to investigate the influence of the dualism of the education system on Islamic education. This dualism has the potential to cause a significant split between Islamic religious education and national education. To overcome this contradiction, the integration of Islamic education into the national education system is an urgent solution. Scholars emphasize the importance of combining the two education systems to prevent further splits. One proposed approach is the development of a third system that combines the positive aspects of traditional and modern education. This integration is expected to create a more holistic and inclusive education system, in accordance with the needs of contemporary society. This study highlights the importance of resolving the dualism of education to improve the quality of education and social harmony in Indonesia.